Comparison of four commercial PRRSV MLV vaccines in herds with co-circulation of PRRSV-1 and PRRSV-2. (April 2019) - Oh, Taehwan; Kim, Hanjin; Park, Kee Hwan; Jeong, Jiwoon; Yang, Siyeon; Kang, Ikjae; Chae, Chanhee
Highlights: The PRRSV-1 and PRRSV-2 MLV vaccine improves growth performance. The PRRSV-1 MLV vaccine cannot reduce PRRSV-1 viremia. The PRRSV-2 MLV vaccine reduces PRRSV-2 viremia. Abstract: The efficacy of four commercial porcine reproductive and respiratory syndrome virus (PRRSV) modified-live virus (MLV) vaccines against respiratory disease was evaluated and compared in pig farms suffering from co-infection with PRRSV-1 and PRRSV-2. All vaccinated groups on average exhibited improved growth rate compared to the unvaccinated pigs. Interestingly, the two groups vaccinated with either of the PRRSV-2 MLV vaccines had a better overall growth rate compared to the pigs vaccinated with either of the PRRSV-1 MLV vaccines. Vaccination of pigs with either of the PRRSV-1 MLV vaccines did not result in reduction of PRRSV-1 or PRRSV-2 viremia whereas vaccination of pigs with either of the PRRSV-2 MLV vaccines resulted in the reduction of PRRSV-2 viremia only. Taken together, the results of this field study demonstrate that a PRRSV-2 MLV vaccine can be efficacious against respiratory disease caused by co-infection with PRRSV-1 and PRRSV-2.